TINGKAT KONSUMSI ZAT GIZI DAN STATUS GIZI MANULA DI SASANA TRESNA WERDHA (STW) PROVINSI BENGKULU - Ismed, Ismed (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
It is estimated that the number of seniors will continue to increase, in line with the decline in infant mortality. One of the important things that need to be considered to anticipate this is to increase attention to the nutritional status of the elderly. Nutritional status is a reflection of the quality of the food it consumes. This study aims to observe the description of nutrient consumption and nutritional status of the elderly in Sasana Tresna Wherda Bengkulu. This research is descriptive in nature, using primary data and secondary data. Data processed manually. The consumption of nutrients for the elderly is still below the recommended dietary allowance or RDA (recommended dietary allowances), especially for vitamin A, vitamin C, Fe, and Ca. The availability of nutrients at the orphanage for calories, protein, and vitamin B is adequate, however, Ca, Fe, vitamin A and vitamin C are not yet as recommended. The nutritional status or stature of the elderly in general is thin, namely 81.3% for men and 62.5% for women. Elderly who consume moderate and poor nutritional substances, nutritional status of the elderly is found thin, but elderly people who consume enough are also underweight.